2005
DOI: 10.1017/s0142716405050307
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of phonological processing skills and reading in bilingual children

Abstract: French/English bilingual children (N=40) in French language schools participated in an 8-month longitudinal study of the relation between phonological processing skills and reading in French and English. Participants were administered measures of phonological awareness, working memory, naming speed, and reading in both languages. The results of the concurrent analyses show that phonological awareness skills in both French and English were uniquely predictive of reading performance in both languages after accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 60 publications
2
32
0
2
Order By: Relevance
“…This is true when the first language shares a similar orthography to English, due to the strong relationship between phonological knowledge and beginning word reading skills in alphabetic texts (Lafrance & Gottardo, 2005). Although having a first language that is nonalphabetic may slow down the development of phonemic awareness compared to those who read the Roman alphabet (Cheung, Chen, Lai, Wong, & Hills, 2001), there is evidence here also of a reciprocal relationship between first-and secondlanguage learning in this respect (Chien, Kao, & Wei, 2008;Kim, 2009;Wang, Perfetti, & Liu, 2005;Wang, Yang, & Cheng, 2009).…”
Section: Second-language Learnersmentioning
confidence: 89%
“…This is true when the first language shares a similar orthography to English, due to the strong relationship between phonological knowledge and beginning word reading skills in alphabetic texts (Lafrance & Gottardo, 2005). Although having a first language that is nonalphabetic may slow down the development of phonemic awareness compared to those who read the Roman alphabet (Cheung, Chen, Lai, Wong, & Hills, 2001), there is evidence here also of a reciprocal relationship between first-and secondlanguage learning in this respect (Chien, Kao, & Wei, 2008;Kim, 2009;Wang, Perfetti, & Liu, 2005;Wang, Yang, & Cheng, 2009).…”
Section: Second-language Learnersmentioning
confidence: 89%
“…Transfer of phonological awareness has received the most research attention among different aspects of metalinguistic awareness. Crosslinguistic effects of phonological awareness have been reported between many language combinations such as Spanish and English (Cisero & Royer, 1995;Durgunoglu, Nagy, & Hancin-Bhatt, 1993), French and English (Comeau et al, 1999;LaFrance & Gottardo, 2005), and even between more distant languages such as Hebrew and English (Wade-Woolley & Geva, 2000), Arabic and English (Wagner, Spratt, & Ezzaki, 1989), and Chinese and English (Gottardo, Yan, Siegel, & Wade-Woolley, 2001). Given these findings, phonological awareness is considered largely independent of specific language experiences (Genessee, Geva, Dressler, & Kamil, 2006).…”
Section: Cross-linguistic Transfer Of Morphological Awarenessmentioning
confidence: 99%
“…Among different aspects of metalinguistic awareness, transfer of phonological awareness has been most extensively investigated (Comeau, Cormier, Grandmaison, & Lacroix, 1999;LaFrance & Gottardo, 2005). This body of research has provided strong evidence that phonological awareness is a common underlying ability that is largely independent of language specific effects (Genesee & Geva, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that bilinguals possess more advanced PA than their monolingual peers (Bialystok, Majumder, & Martin, 2003;Chen et al, 2004;McBride-Chang, Bialystok, Chong, & Li, 2004), and that PA in one language can influence beginning word reading in the other language. For example, rhyme detection in Chinese has been related to phonological skills and reading in English (Gottardo, Yan, Siegel, & WadeWoolley, 2001; see also Bialystok, Luk, & Kwan, 2005; for transfer in FrenchEnglish, see Lafrance & Gottardo, 2005; Turkish-Dutch, see Verhoeven, 2007). The finding on transfer of PA across languages, according to Gottardo et al (2001, p. 539) "points to an underlying process that is not specific to the child's L1 phonology but that is related to the child's ability to reflect on all phonology to which he or she has a minimum level of exposure".…”
Section: Language Precursors Of Literacy Skillsmentioning
confidence: 99%